Digital Business Models The New Value Creation and Capture Mechanisms of the 21st Century - Ronteau, Sébastien (De Gruyter, 2022)
This book provides an overview of how digital players create, exchange and capture value thanks to digital technologies. It describes the key characteristics of various digital business models using different business archetypes. Each chapter is illustrated with examples or mini-case studies and also comprises a toolbox describing strategic tools, canvases and frameworks that help managers analyse a situation and formulate proactive solutions.